THE EFFECT OF USING STUDENT TEAM ACHIEVEMENT DIVISION LEARNING METHOD ON STUDENTS’ ABILITY IN SIMPLE PRESENT TENSE ON THE XI IPA CLASS OF SMA NEGERI 2 LAWE BULAN IN THE ACADEMIC YEAR 2022/2023 - Muliyati Muliyati; Wikiaprian Pinim; Abdul Halim (STKIP USMAN SAFRI KUTACANE, 2024)
This study deals with the effect of using student team achievement division learning method on students’ ability in simple present tense on the XI IPA class of SMA Negeri 2 Lawe Bulan in the academic year 2022/2023. Its objective is to find out whether the use student team achievement division learning method has a significance effect in simple present tense. Population used in this study of class X, XI, and XII were 89 students and samples used in this study of class XI were 21 students. The method used in this study is an experimental method with a one group as pretest and posttest design. This study was carried on using quantitative method. The data was analysed by using t-test. The data was analysed by using t-test. The researcher found the pre-test mean = 55,23, deviation standard = 3,92 and experienced an increase in the post-test mean = 80,95 deviation standard = 3,65. From this analysis, writer found that student team achievement division learning method has significance in teaching simple present tense. It can be proved by the result of the analysis showed that “ ” observed about 49,44 was higher than “ttable” about 1,725 with the level significance is 0,05% it implies that the teacher of english should use Student Team achievement division learning method in teaching simple present tense so that the teaching and learning process can be successful.